(3HMhK GdJShjb (B:s (3eONd efgLj (B-(3JWHjbj (B/s - (3GdRYHj, Ydj adGMs ((3YeGf(B: s (3OGQ UaGA(B, s, 2010)
(3HMhK GdJShjb (B: (3CSS h eaGgje GhdjI, fXe GdeYdheGJ GdJShjbjI , HjFI GdHMhK GdJShjbjI h CfhGY gPg GdHMhK , eUGOQ h WQb LeY GdHjGfGJ , GdYjfGJ h CfhGYgG aj GdHMhK GdJShjbjI , af EYOGO h JUeje GdHMhK GdJShjb jI , GdbjGS h COhGJg aj GdHMhK GdJShjbjI , HMhK GdJShjb GdOhdj , HMhK GdGYdGfGJ(B.s
(3eQGLY U(B.357 (3; edGMb U(B.289s
Keywords: (3EOGQI GdGYeGds; (3COGQI GdeHjYGJs; (3GdJShjbs; (3HMhK GdJShjbs